The Belgariad Volume one - David Eddings (U.S.A Del Ray, The Random House Publishing Group, 2002)
It all begins with the theft of the Orb that for so long protected the West from an evil god. As long as the Orb was at Riva, the prophecy went, its people would be safe from this corrupting power. Garion, a simple farm boy, is familiar with the legend of the Orb, but skeptical in matters of magic. Until, through a twist of fate, he learns not only that the story of the Orb is true, but that he must set out on a quest of unparalleled magic and danger to help recover it. For Garion is a child of destiny, and fate itself is leading him far from his home, sweeping him irrevocably toward a distant tower$1 (Band a cataclysmic confrontation with a master of the darkest magic.s
Keywords: Science Fiction -- Science Fiction; Fantasy -- Fantasy